A busca da paz mundial pela atuação da OIT no enfrentamento ao tráfico de pessoas e seus reflexos no Brasil - Rigato, Juliana Aparecida (2015)
This study has as an objective to analyze the International Labour Organization (ILO) plot in the international community regarding human trafficking confrontation, by considering the transnational organized crime of human trafficking, in all its modalities, listed in Palermo Protocol, as an impediment to world peace, and mainly these actions reflexes in Brazil. For this purpose, it was taken as a start point, specially from Kant's understanding of Peace and human rights' effectiveness, the principles and fundamental rights in labour, the social rights, a reasoning surrounding the seeking for peace, its understanding as a human right and how great its effectiveness can be (the most durable) having no social justice as an International Labour Organization purpose. This, is an example to be followed in this crime's confrotation by its Conventions, Recommendations, Resolutions and publications in the numerous material Offices around the globe. As to Brazilian reality, the difference between human trafficking and smuggling will be explained so that it is possible to understand human trafficking global and interamerican situations. And, consequently, how to confront it based on its "Guide Protocol" and if relevant, not only to present such ILO's reflexes in Brazil, whatever being political, normative, but also to analyze them with a backing on Palermo Protocol and current international and national legislations which directly or indirectly involve the proposed theme